Learning the Tricks of the Trades: Women's Experiences - MacIsaac, Katherine M. R.; Domene, Jose F. (Canadian Journal of Counselling and Psychotherapy, 2013)
This study explored the experiences of 10 women in trades training programs. Using interpretive phenomenological analysis based on 4 focus groups, 9 themes emerged: previous exposure to trades-related tasks, confidence, passion for the work, support from others, the physical nature of the work, the predominantly male environment, proving oneself to others, the “controlled” environment, and job-site discrimination. The results suggest that there is a discrepancy between the social environments of community colleges where the training programs are held and construction job sites. Populations of potential candidates are revealed, and recommendations for practice and future research are discussed.